SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84416-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improved Water Injector Performance in a Gulf of Mexico Deepwater Development Using an Openhole Frac Pack Completion and Downhole Filter System: Case History

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA Gulf of Mexico deepwater subsea development project required seawater injection for pressure maintenance of the producing reservoir. Typical water injector performance in the Gulf of Mexico has been characterized by rapidly declining injectivities that could be partially restored by frequent acid treatments. This type of performance was unacceptable for this field development plan, which required one subsea water injector capable of injecting up to 25,000 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The filtration and particle concentration along the injection induced fractures were visually inspected and pressure information were used to analyze the impact of filtration and fracture growth on the injectivity. Shumbera et al (2003) reported a prolonged period of good injector performance without any injectivity decline by applying a frac-pack completion in a Gulf of Mexico (GoM) water injection project. In other GoM field cases without frac-packs, reported by Sharma et al (2000), the injectivity declined quickly and was affected by reservoir conditions or changes in water quality.…”
Section: Fluid Velocity In Frac-packmentioning
confidence: 99%
“…The filtration and particle concentration along the injection induced fractures were visually inspected and pressure information were used to analyze the impact of filtration and fracture growth on the injectivity. Shumbera et al (2003) reported a prolonged period of good injector performance without any injectivity decline by applying a frac-pack completion in a Gulf of Mexico (GoM) water injection project. In other GoM field cases without frac-packs, reported by Sharma et al (2000), the injectivity declined quickly and was affected by reservoir conditions or changes in water quality.…”
Section: Fluid Velocity In Frac-packmentioning
confidence: 99%
“…Perkins and Gonzales (1985) focused on thermoelastic stress changes caused by the injection of cold water and its impact on fracture growth. Suarez-Rivera et al (2002) investigated experimentally the fracture propagation caused by injecting various types of particle suspensions into large blocks of rocks. The concentration, shape, size, and compressibility of particles greatly affect the fracture-growth rate and leakoff behavior in their study.…”
Section: Performance Of Frac-packed Injectorsmentioning
confidence: 99%